Effects of Octacosanol Extracted from Rice Bran on the Laying Performance, Egg Quality and Blood Metabolites of Laying Hens - Kai Peng; Lei Long; Yuxi Wang; Shunxi Wang (Asian-Australasian Journal of Animal Sciences, 2016)
A 42-d study with 384 Hy-line brown laying hens was conducted to assess the effects of dietary octacosanol supplementation on laying performance, egg quality and blood metabolites of laying hens. Hens were randomly allocated into 4 dietary groups of 8 cages each, which were fed basal diet supplemented with 0 (Control), 9 (OCT9), 18 (OCT18), and 27 (OCT27) mg/kg diet of octacosanol isolated from rice bran, respectively. The experiment was conducted in an environmental controlled house and hens were fed twice daily for ad libitum intake. Laying performance was determined over the 42-d period, and egg quality as well as blood metabolites were estimated on d 21 and d 42. Diets in OCT18 and OCT27 increased (p<0.05) laying rate, egg weight, egg mass, egg albumen height, Haugh unit and eggshell strength on d 42, but decreased (p<0.05) feed conversion rate and levels of total cholesterol, triglyceride and low density lipoprotein cholesterol in the serum as compared to those of Control. Feed intake, yolk color, yolk diameter, eggshell thickness and high density lipoprotein cholesterol were similar (p>0.05) among treatments. Results demonstrate that supplementing 18 to 27 mg/kg diet of rice bran octacosanol can improve laying rate and egg quality and reduce blood lipid of laying hens.